Peningkatan Penerimaan Pajak Melalui Penyuluhan Undang Undang No. 12 Tahun 1994 Tentang Pajak Bumi dan Bangunan - Lego Waspodo (Jurnal Nusantara Berbakti, 2023)
There are several problems to socialize taxation, especially Law No. 12 of 1994 concerning Land and Building Tax, including: How to disseminate and instill an understanding of the importance of taxes for development. How to disseminate and instill public awareness of Law No.12 of 1994 concerning Land and Building Tax. Increasing public understanding of Law No. 12 of 1994 concerning Land and Building Tax is carried out by socialization. Socialization is done with lectures and discussions. Before conducting the lecture, participants were given questionnaires related to understanding and awareness of land and building taxes. At the end of the socialization, participants were distributed the same questionnaire again to find out whether participants' understanding of Law No. 12 of 1994 concerning Land and Building Tax following the training increased or not. This method is expected to increase public understanding and awareness to pay Land and Building Tax obligations.